ANALISIS PERBANDINGAN KINERJA BANK PEMERINTAH, BANK SWASTA, DAN BANK ASING DI INDONESIA - RENO INDRA KUSUMA (JURNAL ILMIAH MAHASISWA AKUNTANSI, 2012)
Soundness of a bank is reflected in the financial statements issued by the bank where such financial statements have been audited by public accounting firms. Health assessment of banks carried out each period. In any assessment of a bank's condition is determined. For banks that have been considered previously can also be assessed whether there is an increase or decrease in health. For banks which, according to health or the health assessment increase does not matter, because that is what is expected and continue to be retained, but the bank is constantly unwell. This study aims to analyze the Government Performance Comparison Bank, Foreign Banks and Private Banks in Indonesia In the Year 2001 to 2010. Population used in this study were all government banks and private banks in Indonesia Stock Exchange. The sampling technique used in this study was purposive sampling because only a selected sample met the criteria only. Analysis techniques use descriptive analysis. CAMEL financial ratio and determine the mean of each ratio. Ratio is CAR (Capital Adequacy Ratio), NPL (Non Performing Loan), ROE (Return On Equity), ROA (Return On Asset), BOPO (Operational Cost Ratio) and LDR (Loan to Deposits Ratio) has the power or the power classification predictions for the state banks experiencing financial difficulties.